2010
DOI: 10.1111/j.1438-8677.2009.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and edge effect determine herbivory risk according to different plant association models

Abstract: We report evidence of hierarchical resource selection by large herbivores and plant neighbouring effects in a Mediterranean ecosystem. Plant palatability was assessed according to herbivore foraging decisions. We hypothesize that under natural conditions large herbivores follow a hierarchical foraging pattern, starting at the landscape scale, and then selecting patches and individual plants. A between- and within-patch selection study was carried out in an area formed by scrubland and pasture patches, connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
(122 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, we have observed that browsing events on C. horrida were concentrated mainly during summer months, after pastures were completely grazed and before the germination period. This is congruent with the findings of Miranda et al (2011), demonstrating that in season-dependent habitats, such as Mediterranean pasturelands, herbivores tend to occupy alternative patches (e.g., Scrubland) when pastures are not productive, i.e., during summer drought.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, we have observed that browsing events on C. horrida were concentrated mainly during summer months, after pastures were completely grazed and before the germination period. This is congruent with the findings of Miranda et al (2011), demonstrating that in season-dependent habitats, such as Mediterranean pasturelands, herbivores tend to occupy alternative patches (e.g., Scrubland) when pastures are not productive, i.e., during summer drought.…”
Section: Discussionsupporting
confidence: 89%
“…Unlike 548 large ungulates, sheep are less able to browse on spiny 549 plants and cause mechanical injuries to single plant 550 individuals, contemporaneously maintaining open 551 spaces suitable for seeds germination and seedlings 552 establishment, as demonstrated also by some experi-553 ments conducted on other plants as Gentiana nivalis L. 554 (Miller et al 1999). Consequently, a possible manage-555 ment regime for C. horrida would be the complete 556 eradication of the most heavy browsers as goats 557 (Campbell and Donlan 2005;Simbaña and Tye 558 2009), the reduction of the other herbivores (deer, 559 mouflon, horses, and donkeys) to densities compatible 560 to the herb biomass grown each year at each site 561 (Donlan et al 2002;Miranda et al 2011), and the 562 maintenance of low densities of controlled sheep 563 (Miller et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The study we present was limited to two months in the Australian summer, and would need to be repeated in winter to assess any seasonal effects. For example, while canopy may act as shelter from high summer temperatures, such patterns may not be seen in winter; equally, seasonal plant availability may affect the relative palatability of patches and thus alter associational effects (as documented by Miranda et al ). Our results suggest that, at larger scales (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…the previous discussion about "neighbour contrast susceptibility"). There are also field observations of browsing patterns supporting this kind of neighbour-mediated effect (Miranda et al 2011).…”
Section: Examples Of Evidencementioning
confidence: 91%